An overview of biodiesel production using recyclable biomass and non-biomass derived magnetic catalysts - Quah, Ray; Tan, Yie Hua; Mujawar, Mubarak; Khalid, M.; Abdullah, E.C.; Nolasco-Hipolito, C. (2019)
© 2019 Elsevier Ltd. All rights reserved. Biodiesel has emerged as a promising alternative to energy sources due to its eco-friendly and renewable nature. However, the issue associated with traditional biodiesel production is the expensive production cost on the industrial scale, mainly contributed by the raw materials. Therefore, catalyst plays an important role with the purpose to speed up the overall biodiesel production rate and minimizing the production cost. Over the course, numerous researches have been done on various types of catalyst in biodiesel production. Henceforth, this review comprises of a comprehensive overview of biodiesel production by discussing the latest trends, that utilizes biomass waste-derived biochar catalyst. Apart from that, the focus of this review will be on magnetic catalyst (derived from both biomass and non-biomass) used in biodiesel synthesis whereby the magnetic catalyst synthesis method and characterisation, as well as compilation of experimental data of different literatures on using magnetic catalyst will be included in the framework of this paper. Moreover, the magnetic catalyst reusability studies are also highlighted in this review. Application of biomass-based magnetic catalyst in biodiesel production may be one of the solutions to overcome the catalyst separation issue and to further the development of economically feasible biodiesel industry and ultimately, transforming the current energy options into a greener and more sustainable sources of energy.